Effects of Injector Configuration on the Detonation Characteristics and Propulsion Performance of Rotating Detonation Engine (RDE) - In-Hoi Koo; Keon-Hyeong Lee; Min-Su Kim; Hyung-Seok Han; Holak Kim; Jeong-Yeol Choi (Aerospace, 2023)
Fuel injection and mixing affect the characteristics of detonation initiation and propagation, as well as the propulsion performance of rotating detonation engine (RDE). A study on the injector is carried out in the present investigation. A rectangular-shaped hole-type fuel injector (RHFI) and slit-type fuel injector (SFI) were designed and compared experimentally at equivalent conditions. The investigation of the detonation propagation modes and the analysis of propulsion performance were carried out using fast Fourier transform (FFT), short-time Fourier transform (STFT), and unwrapped image post-processing. Under 50, 75, and 100 g/s flow rate conditions at an equivalence ratio of 1.0 ± 0.05, the RHFI has relatively stable detonation propagation characteristics, higher thrust, and specific impulse performance. Additionally, the results of the experiment indicate that the number of detonation waves affects performance.